Potential therapeutics specific to c-MET/RON receptor tyrosine kinases for molecular targeting in cancer therapy - Wang Ming-Hai; Padhye Snehal S; Guin Sunny; Ma Qi; Zhou Yong-qing (Acta Pharmacologica Sinica, 2016)
Products of proto-oncogenes c-MET and RON belong to a subfamily of receptor tyrosine kinases that contribute significantly to tumorigenic progression. In primary tumors, altered c-MET/RON expression transduces signals regulating invasive growth that is characterized by cell migration and matrix invasion. These pathogenic features provide the basis for targeting c-MET/RON in cancer therapy. In the last decade, various approaches have been investigated to suppress c-MET/RON-transduced oncogenesis. Among the therapeutics developed, monoclonal antibodies (mAbs) and small-molecule inhibitors (SMIs) have emerged as promising candidates. The mechanism of these therapeutic candidates is the disruption of tumor dependency on c-MET/RON signals for survival. The mAbs specific to hepatocyte growth factor (AMG102) and c-MET (MetMAb) are both humanized and able to block c-MET signaling, leading to inhibition of tumor cell proliferation in vitro and inhibition of tumor growth in xenograft models. The mAb AMG102 neutralizes hepatocyte growth factor and enhances the cytotoxicity of various chemotherapeutics to tumors in vivo. AMG102 is currently in phase II clinical trials for patients with advanced solid tumors. IMC-41A40 and Zt/f2 are RON-specific mAbs that down-regulate RON expression and inhibit ligand-induced phosphorylation. Both mAbs inhibit tumor growth in mice mediated by colon and pancreatic cancer cells. SMIs specific to c-MET (ARQ107 and PF-02341066) are in various phases of clinical trials. Therapeutic efficacy has also been observed with dual inhibitors such as Compound I, which is specific to c-MET/RON. However, a potential issue is the emergence of acquired resistance to these inhibitors. Clearly, development of c-MET/RON therapeutics provides opportunities and challenges for combating cancer in the future.